Simple and economical CALB/polyethylene/aluminum biocatalyst for fatty acid esterification - Cavallaro, Valeria; Ercoli, Daniel Ricardo; Tonetto, Gabriela Marta; Ferreira, María Luján (Polymers for Advanced Technologies)
Candida antarctica lipase B was immobilized for the first time (at the author's knowledge) onto linear low density polyethylene (LLDPE) films. Polymer films were previously bonded to a commercial aluminum sheet using a simple support preparation method. Biocatalyst performance was evaluated in penthyl oleate synthesis at room temperature. Two different catalyst geometries were tested and compared: one aluminum-polyethylene 50 mm × 50 mm foil (50CAT) or near 5 mm × 5 mm aluminum-polyethylene foils (5CAT). The obtained results demonstrate that the biocatalyst obtained with 50 mm × 50 mm aluminum-polyethylene foil or 50CAT is reusable in up to 7 cycles, easy to separate from reaction products, and economical in comparison with commercial Novozym 435. Novel and economical CALB/LLDPE/Al biocatalyst is an attractive alternative for possible applications in a continuous monolithic reactor and future industrial scaling up. Fil: Cavallaro, Valeria. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina Fil: Ercoli, Daniel Ricardo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina Fil: Tonetto, Gabriela Marta. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina Fil: Ferreira, María Luján. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina